Synthesis and Antimicrobial Activity of Some Derivatives of 5-Substituted Indole Dihydropyrimidines - L. C. C. Heda; Rashmi Sharma; C. Pareek; P. B. Chaudhari (E-Journal of Chemistry)
P. Biginelli reported the synthesis of functionalized 3, 4 dihydropyrimidine-2 (1H)-ones via three component condensation of an aromatic aldehyde, urea and ethylacetoacetate. This multicomponent reaction is of much importance due to excellent pharmacological properties of dihydropyrimidines. In this account, we synthesized some halo substituted indole dihydropyrimidines and evaluated their antimicrobial activity. The minimum inhibitory concentration (MIC) was determined by micro dilution technique in Mueller-Hinton broth. The MICs were recorded after 24 hours of incubation at 37 °C. These results are promising, showing these compounds are biologically active.